Retrospective Tertiary Care-Based Cohort Study on Clinical Characteristics and Outcomes of Ceftazidime-Avibactam-Resistant Carbapenem-Resistant Klebsiella pneumoniae Infections - Fatema Ahmed; Betsy Abraham; Nermin Kamal Saeed; Hasan Mohamed Naser; Kannan Sridharan (Critical Care Research and Practice)
Introduction. The advent of ceftazidime-avibactam (CAZ-AVI)-resistant carbapenem-resistant Klebsiella pneumoniae (CRKP) isolates has been steadily documented in recent years. We aimed to identify risk factors of CAZ-AVI-resistant CRKP infection and assess clinical outcomes of patients. Methods. The study retrospectively examined the clinical and microbiological data of patients with ceftazidime avibactam susceptible and ceftazidime avibactam-resistant Klebsiella pneumonia carbapenem-resistant enterobacteriaceae infection to identify risk factors, clinical features, and outcomes using multivariate logistic regression analysis. Results. A total of 152 patients with CRKP infection were enrolled in this study. Patients with CAZ-AVI-resistant CRKP isolates (20/34 = 58.8%) had prior exposure to carbapenems (p=0.003) and had more tracheostomies (16/34 = 47.1%) (p=0.001). Only 8/28 (28.6%) patients with CAZ-AVI susceptible CRKP isolates died amongst those administered ceftazidime-avibactam compared to 49/90 (54.4%) who did not receive the same (p=0.016). 1/9 (11.1%) patients with CAZ-AVI-resistant CRKP isolates who received colistin died compared to 13/25 (52%) who did not receive colistin (p=0.03). There was no association between presence of CAZ-AVI-resistant CRKP isolates and overall mortality (odds ratio: 0.7; 95% CI: 0.3, 1.6), and no independent predictors of risk factors to overall mortality in the group with CAZ-AVI-resistant CRKP isolates were noted. Conclusion. Early advent of CAZ-AVI resistance in CRE isolates highlights the dynamic necessity of routine CAZ-AVI resistance laboratory testing and antimicrobial stewardship programmes focusing on the utilization of all antibiotics. Consolidating the hospital infection control of tracheostomies may help to prevent CAZ resistance in CRKP. Colistin may aid in decreasing of mortality rates among patients with CAZ-AVI CRKP isolates.